Odontoclastic resorption in two dogs - Case report. - Gneidin, José Eduardo Basilio de Oliveira; Gneiding, Beatriz; Lucioli, Joelma; Pimpão, Cláudia Turra; Prado, Antonia Maria do Rocio Binder (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Gneiding J.E.B. de O., Gneiding B., Lucioli J., Pimpão C.T. & Prado A.M. do R.B. [Odontoclastic resorption in two dogs - Case report.] Reabsorção odontoclástica em dois cães - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(3):281-286, 2016. Programa de Pós-Graduação em Ciência Animal, Pontifícia Universidade Católica do Paraná, BR 376 Km 14, São José dos Pinhais, PR 83010-500, Brasil. E-mail: joseeduardo@veterinario.med.br Most often the lesions by odontoclastic resorption (LRO), have been observed in dogs around the globe. Despite being a relatively common disease in cats, it is rarely reported in dogs. Perhaps the lack of reports is related to the non realization of intraoral radiographs for dental treatments in veterinary clinics and hospitals. The LRO is characterized by presenting symptoms such as halitosis, dysphagia, ptyalism, anorexia, dehydration, weight loss, lethargy, head shaking, sneezing and mandibular trismus. These symptoms can often be confused with severe periodontal disease, since in both situations, often makes this a massive amount of dental calculus, which usually complicates the diagnosis by physical examination only. This article describes two cases of LRO in dogs treated at the Hospital Unit of Companion Animals (UHAC), the Pontifical Catholic University of Paraná (PUC-PR) Sant Joseph of Pinhais campus, which showed satisfactory results after extraction treatment.